Target site antibiotic concentrations in orthopedic/trauma extremity surgery: is prophylactic cefazolin adequately dosed? A systematic review and meta-analysis. (4th March 2019) - Sanders, Fay R K; Goslings, J Carel; Mathôt, Ron A A; Schepers, Tim
Abstract : Background and purpose — The incidence of surgical site infections (SSIs) in trauma/orthopedic surgery varies between different body parts. Antibiotic prophylaxis (e.g., with cefazolin) lowers infection rates in closed fracture surgery and in primary arthroplasty. For prophylactic antibiotics to prevent infections, sufficient concentrations at the target site (location of surgery) are required. However, dosage recommendations and the corresponding efficacy are unclear. This review assesses target site cefazolin concentrations and the effect of variation in dose and location of target site during orthopedic extremity surgery. Methods — For this meta-analysis and systematic review, the literature was searched using the following keywords: "cephalosporins, " "orthopedic, " "extremity, " "surgical procedures, " and "pharmacokinetics". Trials measuring target site antibiotic concentrations (bone, soft tissue, synovia) during orthopedic surgery after a single dose of cefazolin were included. Results — The search identified 14 studies reporting on concentrations in the shoulder (n = 1), hip (n = 8), knee (n = 8), or foot (n = 1). A large variation was seen between studies, but the pooled results of 4 studies showed higher concentrations in hip than in knee (mean difference: 4 ug/g, 95% CI 0.8–7). Articles comparing different doses of cefazolin reported higher bone concentrations after 2 g than before, but pooling results did not lead to a statistically significant difference. Interpretation — Although not all results could be pooled, this study shows that cefazolin concentrations are higher in the hip than in the knee. These findings suggest that the dose of prophylactic cefazolin might not be sufficient in distal parts of the extremity. Further research should investigate whether a higher dose of cefazolin can lead to higher concentrations and fewer SSIs.